A transnational history of radio listening groups I: the United Kingdom and United States. Issue 3 (2nd July 2016) - Goodman, David
Abstract : The article offers the first archivally researched, comparative and transnational history of the organised radio listening group in the UK and US, Canada and Australia, from 1928 to the 1950s. It points to several commonalities – listening groups in each nation were supposed to help combat broadcast propaganda, to encourage a more tolerant and worldly perspective in listeners, and to foster skills in articulating and defending personal opinions on public affairs. But it also examines noticeable differences – the somewhat more insistent educational focus in the UK, the emphasis on both self-expression and self-help in the US. The article concludes that the listening group deserves a more prominent position than it has hitherto been granted in the history of broadcasting in these nations and internationally. The eventual failure of group listening to seriously rival individual or familial radio listening should not blind us to the sustained reform energy and high hopes that once surrounded the listening group project.